The hlistic-ecological image of the world versus the mechanicist image - Gloy, Karen; Domínguez Hernández, Javier (Estudios de Filosofía, 1993)
The article describes the mechanicistic paradigm making crisis at present, that has directed both the research on nature and the technical behavior of man in relation to nature, within Westem culture. Philosophy aims at countering with a holistic-organological paradigm, in order to correct the prevailing relationship of man to nature, thereby achieving a relation of equality. The article poses the ethical implications and changes in mental attitude required by such a paradigm.